Polarization modulation based on the hybrid waveguide of graphene sandwiched structure. (28th November 2017) - Yang, Junbo; Chen, Dingbo; Zhang, Jingjing; Zhang, Zhaojian; Huang, Jie
Abstract: Polarization beam splitter (PBS) plays an important role to realize beam control and modulation. A novel hybrid structure of graphene sandwiched waveguide is proposed to fulfill polarization manipulation and selection based on the refractive index engineering techniques. The fundamental mode of TM cannot be supported in this case. However, both TE and TM mode are excited and transmitting in the hybrid waveguide if the design parameters, including the waveguide width and the waveguide height, are changed. The incident wavelength largely affects the effective index, which results in supporting/not supporting the TM mode. The proposed design exhibits high extinction ratio, compact in size, flexible to control, compatible with CMOS process, and easy to be integrated with other optoelectronic devices, allowing it to be used in optical communication and optical information processing.